Satellite glial cells drive the transition from acute to chronic pain in a rat model of hyperalgesic priming - Du, Junying; Yi, Min; Xi, Danning; Wang, Sisi; Liu, Boyi; Shao, Xiaomei; Liang, Yi; He, Xiaofen; Fang, Jianqiao; Fang, Junfan (Frontiers in Molecular Neuroscience, 2023)
Chronic pain is one of the most common clinal syndromes affecting patients’ quality of life. Regulating the transition from acute to chronic pain is a novel therapeutic strategy for chronic pain that presents a major clinical challenge. However, the mechanism underlying pain transitions remains poorly understood. A rat hyperalgesic priming (HP) model, which mimics pain transition, was established decades ago. Here, this HP model and RNA sequencing (RNA-seq) were used to study the potential role of neuroinflammation in pain transition. In this study, HP model rats developed prolonged hyperalgesia in the hind paw after carrageenan (Car) and PGE2 injection, accompanied by obvious satellite glial cell (SGC) activation in the dorsal root ganglion (DRG), as indicated by upregulation of GFAP. RNA-Seq identified a total of differentially expressed genes in the ipsilateral DRG in HP model rats. The expression of several representative genes was confirmed by real-time quantitative PCR (qPCR). Functional analysis of the differentially expressed genes indicated that genes related to the inflammatory and neuroinflammatory response showed the most significant changes in expression. We further found that the expression of the chemokine CXCL1 was significantly upregulated in the rat DRG. Pharmacological blockade of CXCL1 reduced protein kinase C epsilon overproduction as well as hyperalgesia in HP rats but did not prevent the upregulation of GFAP in the DRG. These results reveal that neuroinflammatory responses are involved in pain transition and may be the source of chronic pain. The chemokine CXCL1 in the DRG is a pivotal contributor to chronic pain and pain transition in HP model rats. Thus, our study provides a putative novel target for the development of effective therapeutics to prevent pain transition.